A review on electrical and mechanical performance parameters in lithium-ion battery packs - Rojas, Oscar E.; Khan, Muhammad A. (Elsevier, 2022)
Lithium-ion batteries are the most prominent power source for electric vehicles. The continues use at different environmental conditions demand accurate electrical and mechanical functionality. Most of the research paper published provide information to describe these conditions covering only one or a very few parameters. It leaves aside a holistic and comprehensive study to evaluate performance in lithium-ion battery packs. This review paper presents more than ten performance parameters with experiments and theory undertaken to understand the influence on the performance, integrity, and safety in lithium-ion battery packs. However, when the parameters are reviewed, it is concluded, that vibration and temperature critically affect the electrical and mechanical performance and are inherent to the operation conditions. Through the present work, it was found that limited literature exist that clearly define the influence of temperature and vibration. Therefore, comprehensive research still needs to evaluate the influence of the thermo-mechanical coupled loads on the battery performance. This review concluded that it is fundamental to perform the mentioned research to improve the battery pack performance and safety. In addition, it proposes an innovative technical solution to the automotive industry and can be a novel contribution to academia.
Keywords: lithium-ion battery; State estimation; Design optimization; Mechanical durability; Performance parameters; Battery degradation